Quantitative techniques for decision making in construction - Tang, S. L. (Siu-lam) (Construction and real estate series., 2004)
This book contains mainly quantitative techniques used to assist decision making, including analytic hierarchy process (AHP), decision theories, conditional probabilities and the value of information, inventory modeling, dynamic programming, Monte-Carlo simulation, CYCLONE simulation modeling, information systems and process of decision making in construction.